PENGARUH MP-ASI DINI DI WILAYAH KERJA PUSKESMAS BUKIT KAYU KAPUR TAHUN 2017 - Mustika Mustika; Heru Santosa; Umi Salmah (MMJ (Mahakam Midwifery Journal), 2017)
Abstract Additional feeding before children from six months is not recommended, because it can increase the risk of illness, particularly diarrhea. This research aims to factors that influence on the awarding of the MP-ASI's early work in the area of Bukit Kapur Clinics Dumai Year 2017. This type of research is observational analytic with cross sectional design. The population in this study are all the mothers who have toddlers totaled 122 respondents, where all the population in the sample in this research. The variable in this study is the knowledge, culture, economic status and family support. Data analysis univariate analysis is used with variable frequency distribution research, bivariat chisquare test with, and multivariate logistic regression test with. The results showed that there is the influence of the mother's knowledge of a toddler (p = 0.001 <), culture (p = 0.001 <), family support (p = 0.001 <) against granting MP ASI early and no influence of economic status (p = 0.364), against granting of MP Early BREAST MILK. The most dominant variable influenced the awarding of MP Early BREAST MILK is a cultural variable (p = 0.001; OR < = 8.2 95% CI 2,066-62,598) meaning that the mother of a toddler who believes in culture have risky opportunities 8.2 times larger giving MP Early compared to mother's breast milk toddlers who do not believe in the culture. The conclusion is the absence of any economic status influence against the granting of an early MP-ASI and the influence of the knowledge, culture and family support against the awarding of the MP-ASI early. Expected to health workers in order to deliver health promotion of Exclusive breast milk so that the mother of a toddler can know the exact time in awarding MP Early breast milk. Keywords : knowledge, culture, economic status, family support, early complementary feeding (MP-ASI) ABSTRAK Pemberian makanan tambahan sebelum anak berumur enam bulan tidak dianjurkan, karena dapat meningkatkan resiko terkena penyakit, khususnya diare. Penelitian ini bertujuan untuk Faktor-faktor yang berpengaruh terhadap pemberian MP-ASI dini di wilayah kerja Puskesmas Bukit Kayu Kapur Kota Dumai Tahun 2017. Jenis penelitian adalah analitik observasional dengan menggunakan desain cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang mempunyai balita berjumlah 122 responden, di mana semua populasi tersebut di jadikan sampel dalam penelitian ini. Variabel dalam penelitian ini adalah pengetahuan, budaya, status ekonomi dan dukungan keluarga. Analisis data yang digunakan adalah analisis univariat degan distribusi frekuensi variabel penelitian, bivariat dengan uji chisquare, dan multivariat dengan uji regresi logistik. Hasil penelitian menunjukkan bahwa terdapat pengaruh pengetahuan ibu balita (p = <0,001), budaya (p = <0,001),dukungan keluarga (p = <0,001) terhadap pemberian MP ASI Dini dan tidak ada pengaruh status ekonomi (p = 0,364), terhadap pemberian MP ASI Dini. Variabel yang paling dominan mempengaruhi pemberian MP ASI Dini adalah variabel budaya (p= <0,001;OR=8,2 95%CI 2,066-62,598) artinya ibu balita yang percaya pada budaya memiliki peluang berisiko 8,2 kali lebih besar memberi MP ASI Dini dibanding dengan ibu balita yang tidak percaya pada budaya. Kesimpulannya adalah tidak adanya pengaruh status ekonomi terhadap pemberian MP-ASI dini dan adanya pengaruh pengetahuan, budaya dan dukungan keluarga terhadap pemberian MP-ASI dini. Diharapkan kepada tenaga kesehatan agar dapat memberikan promosi kesehatan tentang ASI Eksklusif sehingga ibu balita dapat mengetahui waktu yang tepat dalam pemberian MP ASI Dini. Kata kunci : pengetahuan, budaya, status ekonomu, dukungan keluarga, pemberian MP ASI